Processing special categories of personal data for the purpose of ensuring bias detection and correction in relation to the high-risk AI systems: an affirmative action measure? - Capellà i Ricart, Anna (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2026)
This article explores whether the measure proposed in article 10(5) of Regulation (EU) 2024/1689 laying down harmonised rules on artificial intelligence, which enables providers of high-risk AI systems to exceptionally process special categories of personal data for the purpose of ensuring bias detection and correction, is a positive action measure. We present the European Union and Spanish’ rules that define positive action and we analyse if the measure under study can be framed in the aforementioned definitions. Moreover, we study the measure in relation to the limits established for positive action by both theCourt of Justice of the European Union and the Spanish Constitutional Court in matters relating to gender equality. Finally, we present some conclusions.
Keywords: positive action; EU AI Act; antidiscrimination; bias; algorithm